2016
DOI: 10.1111/aji.12471
|View full text |Cite
|
Sign up to set email alerts
|

The Pleiotropic Effect of Glycodelin‐A in Early Pregnancy

Abstract: Successful pregnancy depends largely on adequate placentation and maternal tolerance of the fetus. Glycodelin-A is a glycoprotein abundant in the decidua during early pregnancy. It plays an important role in placental development and fetomaternal defense. Glycodelin-A interacts by its unique carbohydrate side chains with the cell surface of various cell types in the human fetomaternal interface, particularly the trophoblasts and the immune cells, and modulates their functions and differentiation to permit succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 85 publications
0
47
0
Order By: Relevance
“…Glycodelin is a protein secreted by the glandular portion of the endometrium that is expressed during and after the implant window (167). This protein has been suggested to play a role as an immunomodulator for the prevention of fetal allograft rejection by maternal cells (168,169). FIGURE 2 | Impact of uterine infusion of human chorionic gonadotrophin (hCG) in classical in vitro fertilization (IVF) patients and in patient suffering from repeated implantation failure (RIF) (at least three embryos have been transferred in these patients, and no pregnancy was observed).…”
Section: Infusion Of Hcg During Embryo Transfermentioning
confidence: 99%
“…Glycodelin is a protein secreted by the glandular portion of the endometrium that is expressed during and after the implant window (167). This protein has been suggested to play a role as an immunomodulator for the prevention of fetal allograft rejection by maternal cells (168,169). FIGURE 2 | Impact of uterine infusion of human chorionic gonadotrophin (hCG) in classical in vitro fertilization (IVF) patients and in patient suffering from repeated implantation failure (RIF) (at least three embryos have been transferred in these patients, and no pregnancy was observed).…”
Section: Infusion Of Hcg During Embryo Transfermentioning
confidence: 99%
“…32 Interestingly, it has been shown that urine-purified and recombinant hCG are able to stimulate the production of LIF both in vitro 33 and human female in vivo. 35,36 Intrauterine infusion of recombinant hCG during the WOI in a non-human primate model significantly up-regulated glycodelin expression by endometrial cells. 9 This protein was suggested to play a putative role as an immune modulator for the prevention of maternal immune rejection to the fetal allograft.…”
Section: Effect Of Hcg On Biomarkers Of Endometrial Receptivitymentioning
confidence: 99%
“…9 This protein was suggested to play a putative role as an immune modulator for the prevention of maternal immune rejection to the fetal allograft. 35,36 Intrauterine infusion of recombinant hCG during the WOI in a non-human primate model significantly up-regulated glycodelin expression by endometrial cells. 37 Although cycling glycodelin has been proposed as a potential marker for endometrial receptivity, the results are still controversial.…”
Section: Effect Of Hcg On Biomarkers Of Endometrial Receptivitymentioning
confidence: 99%
“…They differ only in glycosylation. Initially, three potential N-glycosylation sites were found at positions 28, 63, and 85, but later it turned out that only the first two of them were glycosylated [13,40,41,45]. Mass spectrometric analysis of GdA and glycodelin S (GdS) N-glycans showed significant differences between them.…”
Section: Structure Of Glycodelinmentioning
confidence: 99%